Self–Directed Learning Meaning and Praxis in Classrooms - Singh, Vandana (JOURNAL OF INDIAN EDUCATION, 2010)
The shift from behaviourism to cognitivism in educational psychology has placed an increasing responsibility on learners for their own learning, and self-regulated learning has become a frequent area of educational research. Also, by giving learners more responsibility for their learning can also expect to reduce the burden of teachers for effecting student achievement and teachers can utilise that time in catering to the individual differences among the learners. Therefore, it is important for the teachers to understand the meaning and importance of the Self-directed Learning from the point of view of the various models of the Self-directed Learning. The paper focuses on the ways by which class room practices and conditions can encourage learners to engage in Self-directed Learning. This paper also addresses to instructional issues and ways of fostering Self-directed Learning in the classroom settings.